Geneza kan. 1095 Kodeksu Prawa Kanonicznego Jana Pawła II - Gołębiowska, Anna (Prawo Kanoniczne, 2010)
In the article, the contemporary interpretations of the can. 1095 of the new Code Of Canon Law, which undergone several modifications, were shown. Both the issue of formulating the definitions of mental disorders in the canonical law and the question of “lack of capacity” and psychological capacity for assuming the essential obligations of marriage (as defined by the Church) were explained. Moreover, various opinions of authors on capacity to enter into marriage were presented. Some research on psychological causes which make a person not able to assume the essential obligations of marriage were pointed out. At the same time, there is an explanation of the purpose of marriage according to the teachings of the Second Vatican Council, which resulted in the extension of the list of causes due to which the declaration of nullity might be applied for.